Folklore, Animal Self-Medication, and Phytotherapy–Something Old, Something New, Something Borrowed, Some Things True - Huffman, Michael A. (Planta Medica, 2021)
The use of medicines was long considered by Western schools of thought to be a a domain unique to humans; however, folklore/Traditional Ecological Knowledge (TEK) from around the world suggests that animals have also long provided inspiration for the discovery of some medicinal plants used to treat humans and their livestock. Searching for medicinal knowledge from animals depends on the recognition of their ability to select and effectively use medicinal plants to prevent or actively ameliorate disease and other homeostatic imbalances. The interdisciplinary field of animal self-medication is providing scientific evidence for this ability in species across the animal kingdom and lends support to animal-origin medicinal plant folklore and recent ethnomedicinal information. Here, 14 case studies of purported animal-inspired plant medicines used by cultures around the world are presented together with ethnomedicinal and pharmacological evidence. Based on this evidence, the diversity and potential mode of self-medicative behaviors are considered. Over 20 animal species, including llama, sloth and jaguar in South America, reindeer and yak in Eurasia, langur and macaque in Asia, and chimpanzee, wild boar, porcupine and elephant in Africa, are linked to these case studies, representing a variety of potential preventative or therapeutic self-medicative behaviors. These examples provide an important perspective on what is likely to have been a much wider practice in the development of human traditional medicine. A role for animal self-medication research in the rejuvenation of old therapies and possible new discoveries of phytotherapies for human and livestock health is encouraged.
Keywords: phytotherapy; traditional medicine; animal behavior; folklore; traditional ecological knowledge; zoopharmacognosy